The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4155/fmc.14.63
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Therapeutic Development for Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy (SMA) is a leading genetic cause of infant mortality. The disease originates from low levels of SMN protein due to deletion and/or mutations of SMN1 coupled with the inability of SMN2 to compensate for the loss of SMN1. While SMN1 and SMN2 are nearly identical, SMN2 predominantly generates a truncated protein (SMNΔ7) due to skipping of exon 7, the last coding exon. Several avenues for SMA therapy are being explored, including means to enhance SMN2 transcription, correct SMN2 exon 7 spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 146 publications
(178 reference statements)
0
50
0
Order By: Relevance
“…Among several hundred targets examined thus far, ISS-N1 remains the most effective target for an ASO-mediated stimulation of SMN2 exon 7 inclusion [89]. Numerous studies employing various mouse models have independently validated the in vivo efficacy of ISS-N1-targeting ASOs [23]. The recently approved ISS-N1-targeting drug for SMA, Nusinersen (synonyms: ISIS-SMN Rx , IONIS-SMN Rx and Spinraza™), is a modified oligonucleotide that carries phosphorothioate backbone and encompasses methoxyethyl modification at the 2′-hydroxyl position of the revealed that the sequence spanning from the 10 th to 24 th positions of intron 7 is highly inhibitory for exon 7 inclusion [85].…”
Section: Regulation Of Smn Exon 7 Splicingmentioning
confidence: 99%
See 2 more Smart Citations
“…Among several hundred targets examined thus far, ISS-N1 remains the most effective target for an ASO-mediated stimulation of SMN2 exon 7 inclusion [89]. Numerous studies employing various mouse models have independently validated the in vivo efficacy of ISS-N1-targeting ASOs [23]. The recently approved ISS-N1-targeting drug for SMA, Nusinersen (synonyms: ISIS-SMN Rx , IONIS-SMN Rx and Spinraza™), is a modified oligonucleotide that carries phosphorothioate backbone and encompasses methoxyethyl modification at the 2′-hydroxyl position of the revealed that the sequence spanning from the 10 th to 24 th positions of intron 7 is highly inhibitory for exon 7 inclusion [85].…”
Section: Regulation Of Smn Exon 7 Splicingmentioning
confidence: 99%
“…Numerous studies employing various mouse models have independently validated the in vivo efficacy of ISS-N1-targeting ASOs [23]. The recently approved ISS-N1-targeting drug for SMA, Nusinersen (synonyms: ISIS-SMN Rx , IONIS-SMN Rx and Spinraza™), is a modified oligonucleotide that carries phosphorothioate backbone and encompasses methoxyethyl modification at the 2′-hydroxyl position of the sugar moiety [23]. The above-mentioned modifications are known to enhance the in vivo stability of oligonucleotides.…”
Section: Regulation Of Smn Exon 7 Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…These crucial findings, together with others, suggest that astrocytes, sensory neurons, Schwann cells and skeletal muscle may all contribute to the expression of the disease and its associated motor neuron loss [28,29,27,30,25,31,32]. Additional evidence of the potential key role of non–motor neuronal cells in SMA pathogenesis was recently provided by an effort to up-regulate SMN protein, introducing the wild-type SMN1 gene [33-36], or by modulating SMN2 splicing with oligonucleotides or small molecules in mice (for review see [4], [37,38]. Several recent studies have demonstrated that these strategies can significantly increase survival of SMA mice [39-44,38].…”
Section: Therapeutic Implications In Non-motor Neuron Cell Typesmentioning
confidence: 99%
“…Here we describe an example of ASO-mediated splicing correction in Spinal Muscular Atrophy (SMA), a leading genetic cause of infant mortality (3133). SMA is caused by the loss of the Survival Motor Neuron 1 ( SMN1 ) gene (34).…”
Section: Introductionmentioning
confidence: 99%